Development of Database Covering Agri – Fishery in the Province of Apayao - Razalan, Lloyd Mark; Raralio, Darwin (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study aimed to develop and implement a centralized database system covering the agri-fishery sector of the Province of Apayao to address persistent challenges related to fragmented, inaccurate, and inaccessible agricultural and fisheries data. Anchored on the Input–Process–Output (IPO) framework, the study employed a developmental research design focusing on database planning, analysis, design, development, implementation, evaluation, and maintenance. Data were collected from government officials, agricultural extension workers, farmers, fisherfolk, and data managers using structured interviews, surveys, observations, and document reviews, and were analyzed through descriptive statistics, content analysis, and gap analysis. The results showed that the developed relational database successfully consolidated data on crop production, aquaculture, land use, farmer and fisherfolk profiles, and market information into a single, user-friendly platform. The system improved data accessibility, reduced redundancy in reporting, and enabled real-time monitoring and evidence-based decision-making for government agencies and stakeholders. Agricultural extension workers reported increased operational efficiency due to reduced administrative workload. However, challenges related to limited digital literacy, inconsistent internet connectivity in remote areas, and sustainability concerns regarding long-term funding and technical support were identified. The study concludes that a well-structured agri-fishery database can significantly enhance data management, policy formulation, and program implementation in the province. The study is aligned with Sustainable Development Goals 8 (Decent Work and Economic Growth), 9 (Industry, Innovation and Infrastructure), and 12 (Responsible Consumption and Production) by supporting data-driven agricultural planning and digital infrastructure development. Overall, the study contributes to institutional and socio-economic sustainability by strengthening data governance, improving service delivery, and supporting sustainable agricultural and fisheries development in Apayao.